please answer this question briefly
Attachments:
![](https://hi-static.z-dn.net/files/db2/f97b2b13cc5bf28f9fe008a2d40f6647.jpg)
Answers
Answered by
2
a.p has same difference between all term
so, a2-a = a3-a2
2k-1-k = 2k+1 -2k+1
=> k-1 = 2
=> k=3
hope it helps you.....✌✌
Answered by
0
Step-by-step explanation:
if a,b,c terms are in A.P
THEN 2B=A+C
SO
2(2K-1)=2K+1+1
4K-2=2K+1+K
K=3
SO OPTION IS B)3
Similar questions
Science,
6 months ago
English,
6 months ago
Science,
6 months ago
Biology,
1 year ago
Social Sciences,
1 year ago